2017
DOI: 10.1080/08958378.2017.1366602
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical safety assessment of SPX-101, a novel peptide promoter of epithelial sodium channel internalization for the treatment of cystic fibrosis

Abstract: SPX-101, a novel peptide promoter of ENaC internalization, elicited no adverse effects at doses up to the MFD and in excess of the highest preclinical efficacious and expected clinical doses. In contrast to channel blockers like amiloride and derivative small molecules, SPX-101 does not achieve significant systemic circulation, thus doses are not limited due to toxic side effects like hyperkalemia and weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For instance, the P2Y 2 receptor agonist denufosol failed to show replicable results in phase III clinical trials [52], and to the best of our knowledge, there are, at the moment, no chemical compounds in clinical trials that target purine metabolism. Third, compounds associated with SPLUNC1, while in the early stages of clinical tests, have been producing positive results [27,53,54]; correspondingly, we focused on the relationships between ENaC, ASL, SPLUNC1 and PI(4,5)P 2 . Fourth, our results indicate that the components used in our model are sufficient to capture the phenomena of interest here.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the P2Y 2 receptor agonist denufosol failed to show replicable results in phase III clinical trials [52], and to the best of our knowledge, there are, at the moment, no chemical compounds in clinical trials that target purine metabolism. Third, compounds associated with SPLUNC1, while in the early stages of clinical tests, have been producing positive results [27,53,54]; correspondingly, we focused on the relationships between ENaC, ASL, SPLUNC1 and PI(4,5)P 2 . Fourth, our results indicate that the components used in our model are sufficient to capture the phenomena of interest here.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of SPX-101 to neonatal transgenic mice overexpressing the β-subunit of ENaC (one of the most widely used models of CF lung disease) improved survival from roughly 45% to 92% at the most efficacious dose. Importantly, safety data in murine and canine models did not demonstrate any adverse events, even in doses up to the maximum feasible dose [73]. At therapeutically meaningful doses, SPX-101 did not produce hyperkalemia, alter body weight, urinalysis measures, or blood chemistry, as peptide delivery to the lung offers some tissue specificity.…”
Section: Enac Inhibitors In Developmentmentioning
confidence: 99%
“…This is because these small molecule inhibitors of ENaC enter the systemic circulation where they engage ENaC in the kidney thereby inducing potassium-sparing diuresis. Nebulized SPX-101 was tested in toxicology trials in rats and dogs and found to have no impact on serum potassium concentrations and was rapidly removed from systemic circulation [18,39]. Moreover, in clinical trials in healthy volunteers and adult patients with cystic fibrosis SPX-101 was not associated with any relevant changes in serum or urinary potassium (manuscripts in preparation).…”
Section: Discussionmentioning
confidence: 99%